(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The description can be perceived as a decoration of the discourse, an ornament pertaining to many images. Realist writers wanted to explain reality, i.e., paint everyday scenes without embellishing them; for this reason, they relied on describing them.In reality, many descriptions dot the pages of literary works. We have studied their nature, their history, their diegetic functions through the work of Philippe Claudel, La Petite fille de Monsieur Linh. A novel where the description takes on its scope and importance through passages and images that are not lacking in originality.Philippe Claudel establishes complex relationships between real facts and the poetic aesthetics of prose, in the romantic possibilities where he slowly leads us into enchanting universes.We have attempted in this study to demonstrate the place occupied by description in the hyperbolic universe of the aesthetic ornaments of a work and in particular in La Petite fille de Monsieur Linh. Added to this is its essential role in understanding events.